Cooperative Game Theory: Examining Promise, Trust and Contract Interplay - Lazuardi Al-Muzaki (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – This study aims to examine the interplay between promise, trust, and contract in cooperative game theory under conditions of moral hazard and information asymmetry. It seeks to identify how intrinsic promise-keeping behavior influences agent decisions, utility distribution, and social surplus maximization, with application to public–private contracting contexts. Methodology – Building on Chen’s (2000) framework, the study develops a cooperative game model applied to a case study of a local government–contractor bridge project governed by an incomplete contract. The model stresses a critical value parameter ( ) representing the contractor’s intrinsic utility from keeping a promise. A numerical simulation is conducted using hypothetical parameters to evaluate how varying impacts contractor behavior (honest vs. cheating), parties utility, and social surplus. Findings – The simulation identifies a behavioral tipping point at , below which opportunistic behavior dominates, reducing social surplus and government utility. When meets or exceeds this threshold, honest behavior becomes utility-maximizing for the contractor, significantly improving outcomes for both parties. Originality – The study’s novelty lies in simulating the behavioral threshold of the trust parameter ( ) within a cooperative game model, quantifying its impact on agent behavior and social surplus under incomplete contracts. Practical implications – The findings suggest that intrinsic trust mechanisms, such as long-term partnerships, reputation systems, and community accountability, can serve as cost-effective substitutes or complements to formal enforcement in incomplete contracts.